Peningkatan Literasi Digital dan Menulis Artikel Ilmiah Guru dengan Memanfaatkan Artificial Intelligence - M. Miftach Fakhri; Dary Mochamad Rifqie; Asriadi Asriadi; Asri Ismail; Andika Isma; Della Fadhilatunisa (PT. Global Research Collaboration, 2024)
The purpose of this service discusses efforts to increase the capacity of teachers in writing scientific articles by utilising Artificial Intelligence (AI). Through an Action Research approach, teachers are directly involved in the process of improving and developing their abilities in digital literacy and scientific article writing techniques. The community service stage involves systematic steps to achieve the goal of improving teachers' ability to utilise AI. The results of the community service show an increase in teachers' ability to write scientific articles, which is expected to improve the quality of their scientific publications. With a better understanding of AI, teachers are expected to integrate this technology effectively in learning, creating a more innovative and adaptive learning environment. In conclusion, this service makes a real contribution in improving teachers' digital literacy and scientific article writing skills, and provides a foundation for the development of future service activities.